Pregnancy management in patients with uterine fibroids. Case report - Iuliia E. Dobrokhotova (IP Berlin A.V., 2021)
Uterine fibroids (UF) are the most common tumor in women of reproductive age. The growth of myomatous nodes during pregnancy is non-linear and mainly occurs in the first trimester. In most cases, UF do not burden the course of pregnancy. Large size (5 cm), retroplacental location, and/or deformity of the uterine cavity by the myomatous node are associated with increased risks of spontaneous miscarriage, placental abruption, bleeding, preterm birth, and cesarean section. Myomectomy during pregnancy is undesirable, with the development of pain syndrome, the use of acetaminophen is safe. Indications for cesarean section in UF are the presence of a large size of fibroids that prevent delivery through the natural birth canal, red degeneration of myomatous nodes, torsion of the subserous myomatous node (degree 2C).